Recursos pedagógicos utilizados nas aulas práticas de educação física nos anos finais do ensino fundamental - Santos, David Pantoja dos (Brasil, 2024)
Physical Education as a discipline became mandatory from the 1988 federal constitution, and left its recreational character only from LDB No. implemented in practice, contributing to the full development of motor, cognitive and affective-social functions. The objective of this study was to investigate the existence and use of the pedagogical resources necessary for the practical classes of Physical Education in the final years of elementary education in public schools in the city of Parintins-AM. The sample consisted of 04 teachers, of both sexes, aged between 20 and 40, and 64 students aged between 11 and 15 years old in the city of Parintins-AM. We used two questionnaires as instruments, one for the students and the other for the teachers, with open and semi-open questions, with questions referring to the quantity and quality of materials available for the practice of PE, the positioning of teacher and students regarding available resources and their use in practical classes. With this, teachers reported the main factors that negatively influence practical classes, such as: the scarcity of materials, adequate space and maintenance of spaces and materials. The students pointed out that most participate in classes, that the school offers an adequate structure, that there are materials in quantity and sufficiency, but of reasonable quality for practical classes. The findings of the present study highlight that there are pedagogical resources for practical Physical Education classes, but they do not show a significant percentage, as there is a small margin of difference in the responses in relation to the adequate structure, quantity and quality of material resources. For future studies related to the subject, it is suggested that more observation methods can be used to analyze the data in a more concrete way so that it can be consistent with the school reality.